2022
DOI: 10.1177/03635465211069356
|View full text |Cite
|
Sign up to set email alerts
|

Early and Delayed Surgery for Isolated ACL and Multiligamentous Knee Injuries Have Equivalent Results: A Systematic Review and Meta-analysis

Abstract: Background: Early surgery for acute ligamentous injuries has recently shown good clinical and functional outcomes. Purpose: To assess the advantages of early vs delayed surgery in patients undergoing isolated anterior cruciate ligament (ACL) or multiligament-injured knee (MLIK) surgery. Study Design: Meta-analyses of Level 1, 2, and 3 studies; Level of evidence, 4. Methods: A systematic search was performed via PubMed, EMBASE, and Cochrane for studies reporting outcomes of timing of surgery after isolated ACL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 63 publications
0
11
1
Order By: Relevance
“…The median time from injury to initial ligament/capsule surgery was 64 days, with an IQR of 23 to 190 days. The ideal timing for surgery has yet to be conclusively determined [25][26][27] . Early surgery has been associated with an increased risk of loss of motion 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…The median time from injury to initial ligament/capsule surgery was 64 days, with an IQR of 23 to 190 days. The ideal timing for surgery has yet to be conclusively determined [25][26][27] . Early surgery has been associated with an increased risk of loss of motion 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, the expectation of return to sports activity among them will be higher which is within 1 year following complete ACLR post-operative rehabilitations (Fabricant et al, 2016). A recent systematic review with meta-analysis which involved 2093 patients documented that there were no difference in clinical and functional outcomes between those receiving early or delayed (3 and 6 weeks cut-off) ACLR surgery for isolated ACL injury (Vermeijden et al, 2022). However, despite this report, the question on the success of return to sports remains unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of high rates of secondary injuries after knee dislocations are further pronounced in the high rates of patients (42%) who develop osteoarthritis after knee dislocations 62 . A recent systematic review showed that patients treated early had significantly lower rates of secondary injury; however, further studies are needed to compare functional outcomes between patients treated by acute versus delayed ligamentous repair or reconstruction 63 . However, not all patients can have an early repair, such as the case of our patient where significant knee swelling, and the healing of the tendon repair was a barrier to immediate surgical intervention.…”
Section: Sports Medicinementioning
confidence: 99%